Pemanfaatan Budidaya Maggot Sebagai Pengelolaan Limbah Dapur Bernilai Ekonomis - Putu Adnyaswari Devi; I Gusti Ayu Alit Mirah Pradnyadewi; Anak Agung Ayu Ratih; Ida Bhujangga Mas Sintya Vaisnava; A. A Sagung Shilpa Gayatri Iswari (Lembaga Penelitian, Universitas Warmadewa, 2025)
Tegal Tugu Village faces the problem of managing organic waste which has not provided significant economic value, even though it has implemented the 3R method and maggot cultivation (Black Soldier Fly larvae/BSF) as an environmental solution. This research aims to develop an effective and efficient maggot cultivation method to optimize organic waste management while increasing village income. This research uses a qualitative approach with data obtained through interviews and observations at TPS 3R Tri Buana Asri. Data analysis techniques were carried out by mapping cultivation media needs, designing a maggot cultivation system, and evaluating harvest results as catfish feed. The research results show that a plastic tub-based cultivation media design with a liquid drainage system can reduce odors, increase the efficiency of maggot production, and produce quality feed for catfish. The contribution of this research lies in optimizing the management of organic waste into sustainable economic resources. The practical implications include opportunities to increase village income through diversification of maggot products as well as the promotion of circular economy concepts that support sustainable environmental management.